2011
DOI: 10.1517/13543784.2011.562189
|View full text |Cite
|
Sign up to set email alerts
|

S/GSK1349572, a new integrase inhibitor for the treatment of HIV: promises and challenges

Abstract: S/GSK1349572 represents a new, unboosted, once-daily INI in development with distinct pharmacokinetics and resistance profile, which has showed promising potency and tolerability in the first clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This increase in dolutegravir exposure is not anticipated to impact clinical safety, and therefore dolutegravir can be taken with or without food and without regard to fat content. D olutegravir (DTG; S/GSK1349572) is an integrase inhibitor for the treatment of HIV infection, does not require boosting with ritonavir, and possesses activity against raltegravir-resistant strains (3,4). DTG is currently in phase III clinical development at a dose of 50 mg once daily in treatment-naive and integrase-naïve treatment-experienced subjects and at 50 mg twice daily in subjects with resistance to raltegravir or elvitegravir.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in dolutegravir exposure is not anticipated to impact clinical safety, and therefore dolutegravir can be taken with or without food and without regard to fat content. D olutegravir (DTG; S/GSK1349572) is an integrase inhibitor for the treatment of HIV infection, does not require boosting with ritonavir, and possesses activity against raltegravir-resistant strains (3,4). DTG is currently in phase III clinical development at a dose of 50 mg once daily in treatment-naive and integrase-naïve treatment-experienced subjects and at 50 mg twice daily in subjects with resistance to raltegravir or elvitegravir.…”
mentioning
confidence: 99%
“…To avoid selection bias, the first 18 subjects who were enrolled in part 1 who still met all eligibility criteria continued to part 2. Serial blood samples for PK analysis were collected predosing and 1, 2,3,4,5,6,8, 12, 24, and 48 h postdosing. There was a washout period of 7 days between doses.…”
mentioning
confidence: 99%
“…Integrase inhibitors (INIs) are mainly metabolized by uridine diphosphate glucuronosyltransferase (UGT) 1A1. These INIs are neither inducers nor inhibitors of CYP3A4 (4,5). Therefore, they presumably do not interact with CNIs (2).…”
Section: Discussionmentioning
confidence: 99%
“…Its global phase III trials are currently in progress. During a phase II trial with HAART-naïve subjects, its non-inferior efficacy was demonstrated to be not inferior to that of efavirenz (NNRTI) (Sustiva, Bristol-Myers Squibb Pharma Company, New York, USA) (5). In vitro studies have raised the curious possibility that DTG could have the potential of a higher genetic barrier to resistance than RAL, in the setting of INI-naïve patients (9) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation